GAMBARAN POLA ASUPAN MAKANAN PENDAMPING ASI DAN ERUPSI GIGI ANAK USIA 12 – 24 BULAN DI PUSKESMAS TELING - Paparang, Ferdinand (e-GiGi, 2014)
Abstract: Additional food intake in children aged 12 months - 24 months is one of the factors to achieve optimal growth and development . It is also associated with the eruption of deciduous teeth . The pattern of food intake provides a description of the form of food and frequency of feeding in addition to breast-feeding ( breast milk ) . Tooth eruption is a process by which a dental crown appears on the surface of the gums . This study aims to describe the pattern of food intake on tooth eruption children aged 12-24 months . This is a descriptive study and sample selection is done by means of purposive sampling The results showed Preview pattern of food intake of children aged 12-24 months at the health center as seen from the top Teling types and frequency of eating food that is the subject of research in accordance with the type of food that reaches 100% while eating frequency corresponding to approximately 79.24%. Picture of tooth eruption patterns of children aged 12-24 months at the health center that has erupted Top Teling complete approximately 60.38% while that is not the complete eruption of approximately 39.62%. Keywords: food intake, tooth eruption. Abstrak: anak usia 12 bulan-24 bulan merupakan salah satu faktor tercapainya pertumbuhan dan perkembangan yang optimal. Hal ini juga berhubungan dengan proses erupsi gigi desidui. Pola asupan makanan memberikan gambaran mengenai bentuk makanan dan frekuensi pemberian makan selain pemberian air susu ibu ( ASI ). Erupsi gigi merupakan proses dimana mahkota gigi muncul di permukaan gusi. Penelitian ini bertujuan untuk mengetahui gambaran pola asupan makanan dan pola erupsi gigi anak usia 12-24 bulan. Penelitian ini bersifat  deskriptif dan pemilihan sampel dilakukan dengan cara purposive sampling. Hasil penelitian menunjukkan Gambaran Pola asupan makanan anak usia 12 – 24 bulan di Puskesmas Teling Atas yang dilihat dari jenis makanan dan frekuensi makan yakni subjek penelitian dengan jenis makanan yang sesuai mencapai 100% sedangkan untuk frekuensi makan yang sesuai sekitar 79,24%. Gambaran pola erupsi gigi anak usia 12 – 24 bulan di Puskesmas Teling Atas yang sudah erupsi lengkap sekitar 60,38% sedangkan yang tidak erupsi lengkap sekitar 39,62%. Kata kunci: Asupan makanan, erupsi gigi.